1992
DOI: 10.2307/1938721
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leaf Litter on Early Seedling Establishment in a Tropical Forest

Abstract: The presence of leaf litter of different depths within a tropical forest creates many different microsites for plant establishment. The amount and distribution of leaf litter within a forest can influence patterns of plant establishment. In this study, we determined the spatial variability in leaf litter in the forest understory, and investigated how different litter depths (bare, 1, 6, and 12 cm) affected the establishment of several tropical tree species in both growth house (sun and shade) and field (gap an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
302
1
25

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(335 citation statements)
references
References 29 publications
7
302
1
25
Order By: Relevance
“…In tropical rain forest both leaf litter cover and leaf litter depth contribute to microenvironmental heterogeneity and are spatially unpredictable even at scales of few meters (Molovsky & Augspurger 1992, Cintra 1997a). In the Reserva Ducke, the microsite variation in leaf litter depth did not affect palm species richness, however it was inversely related to palm abundance, suggesting that palms are in higher numbers in areas of shallow leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical rain forest both leaf litter cover and leaf litter depth contribute to microenvironmental heterogeneity and are spatially unpredictable even at scales of few meters (Molovsky & Augspurger 1992, Cintra 1997a). In the Reserva Ducke, the microsite variation in leaf litter depth did not affect palm species richness, however it was inversely related to palm abundance, suggesting that palms are in higher numbers in areas of shallow leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of relatively nutrient-rich disturbance-generated litter and fine-root and plant mortality (Parrotta and Lodge 1991;Silver and Vogt 1993) can affect rates of litter decomposition and mineralization, leading to temporary alterations in ecosystem-scale carbon (C) and nutrient cycling rates (Sanford and others 1991) and increasing nutrient export in stream water (Schaefer and others 2000). These modifications of the physical and chemical environment of the forest floor can also affect processes such as seed germination, seedling establishment, and the relative ranking of species, often in complex and speciesspecific ways (Facelli and Carson 1991;Guzmá nGrajales and Walker 1991;Molofsky and Augspurger 1992;Everham and others 1996;Harrington and others 1997). Although these observational, experimental, and modeling studies have demonstrated that hurricane litter can affect many ecosystem processes, the length of time that this hurricane-generated forest floor mass remains elevated above predisturbance levels, and thus has a direct physical and biogeochemical effect on ecosystem processes, is poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…This was another unexpected result since for these species the germination success of scarified seeds in germination chambers can be high (83% in I. rubriflora and 94% in I. purpurea; J. Astegiano, unpublished data). On the other hand, since species differ in seed mass and larger-seeded species may produce larger seedlings that may be able to emerge from deeper soil levels or more developed litter layers (Jurado and Westoby, 1992;Molofsky and Augspurger, 1992;Pearson et al, 2003), we expected higher probability of emergence in I. purpurea. We propose that the generally negative effect of litter on plant regeneration, by either preventing germination or suppressing seedling growth and which may be independent of seed size (Dalling and Hubbell, 2002;Fenner and Thompson, 2005), might explain the similar probability of emergence recorded for these two species of Ipomoea.…”
Section: Discussionmentioning
confidence: 83%